Potential Application of Photosensitizers With High-Z Elements for Synergic Cancer Therapy - Sarbadhikary, Paromita; George, Blassan P.; Abrahamse, Heidi (Frontiers in Pharmacology, 2022)
The presence of heavy elements in photosensitizers (PS) strongly influence its electronic and photophysical properties and hence conjugation of PS with a suitable element is regarded as a potential strategy to improve its photodynamic properties. Moreover, PSs conjugated to metal ion or metal complex and heavy atoms like halogen have attracted considerable attention as promising agents for multimodal or synergistic cancer therapy. These tetrapyrrole compounds depending on the type and nature of the inorganic elements have been explored for photodynamic therapy (PDT), chemotherapy, X-ray Photon Activation Therapy (PAT) and radiotherapy. Particularly, the combination of metal-based PS and X-ray irradiation has been investigated as a promising novel approach for treating deep-seated tumors, which in the case of PDT is a major limitation due to low light penetration in tissue. This review will summarize the present status of evidence on the effect of insertion of metal or halogen on the photophysical properties of PS, and the effectiveness of various metal and halogenated PSs investigated for PDT, chemotherapy and PAT as mono and/or combination therapy.